1987
DOI: 10.1016/s0022-5347(17)43582-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Some Calcium Channel Blockers on Isolated Human Penile Erectile Tissues

Abstract: The effects of the calcium channel blockers (CCBs) verapamil, nifedipine and diltiazem on contractile activation of isolated human penile erectile tissues were investigated. Specimens of the corpus spongiosum (CS) and corpora cavernosa (CC) were obtained from men with a history of normal penile erection undergoing cystourethrectomy because of bladder malignancy. Preparations were mounted in organ baths and isometric tension was recorded. Deprivation of extracellular calcium abolished electrically induced contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 14 publications
3
29
0
1
Order By: Relevance
“…[144][145][146] However, a recent double-blind, randomized study, involving 1549 patients, failed to reveal any significant effect of an Ang-II receptor blockers or an ACE inhibitor on ED. 148,149 CSM contracted by a-adrenergic agonists in vitro. However, ICI of CCBs in dogs was less effective and had more side effects compared to papaverine.…”
Section: Endogenous Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…[144][145][146] However, a recent double-blind, randomized study, involving 1549 patients, failed to reveal any significant effect of an Ang-II receptor blockers or an ACE inhibitor on ED. 148,149 CSM contracted by a-adrenergic agonists in vitro. However, ICI of CCBs in dogs was less effective and had more side effects compared to papaverine.…”
Section: Endogenous Mechanismsmentioning
confidence: 99%
“…153,154 Although the side effect of ICI of CCBs was comparable to other agents, CCBs may not be as effective as blockade of a-adrenoceptors. 148,153,154 Blockage of Ca 2 þ -sensitizing pathway (mainly RhoA/ROCK). Ten years ago, the inhibition of ROCK by ICI of Y-27632 was found to induce an erectile response in rats.…”
Section: Endogenous Mechanismsmentioning
confidence: 99%
“…13,14 Spontaneous contractions (Figure 2a) have been recorded from corpus cavernosum smooth muscle (CCSM) and corpus spongiosum smooth muscle from various mammals, including man. [14][15][16] The mechanisms underlying these contractions are spontaneous action potentials and associated transient increases in [Ca 2 þ ] i (Figures 2b and c) The contractions depend on extracellular Ca 2 þ , and are blocked by L-type Ca 2 þ channel blockers, and by drugs, which hyperpolarize the cells, demonstrating the important role of L-type Ca 2 þ channels in the generation of spontaneous activity.…”
Section: Erectile Smooth Musclementioning
confidence: 99%
“…5,6 In the ongoing search for agents that have the capacity of relaxing cc smooth muscle cells and thereby have a possible role in the pharmacological treatment of erectile dysfunction, multiple, in vivo and in vitro studies on cc smooth muscle have been carried out. These studies have demonstrated relaxatory response of cc smooth muscle to naturally occuring compounds such as prostaglandin, 7 vasoactive intestinal polypeptide 8 and pharmacological agents such as papaverine, 9 phosphodiesterase inhibitors, 10 calcium channel blocking compounds, 11 potassium channel openers 12,13 and alpha adrenoceptor blocking agents. 14,15 Abanoquil, UK-52,046 (4-amino-6,7-dimethoxy-2(1,2,3,4-tetrahydro-6,7-dimethoxyisoquinol-2-yl) quinoline methanesulphonate) ( Figure 1) is a novel alpha adrenoceptor antagonist with a high selectivity to the alpha-1 subtype.…”
Section: Introductionmentioning
confidence: 99%